Three-dimensional ferromagnetic super-hydrophobic material and preparation method and application thereof
The superhydrophobic nickel layer is formed on the three-dimensional structure through laser selective metallization and electroplating methods, which solves the problem that the two-dimensional manufacturing method cannot be applied to three-dimensional line conduction and the pervious corrosion of the nickel layer, and achieves high conductivity and weather resistance. Preparation of three-dimensional ferromagnetic superhydrophobic materials, suitable for a variety of electronic products.
Patent Information
- Application Number
- CN202411288902.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing two-dimensional manufacturing methods cannot be applied to circuit conduction of three-dimensional structures, which limits the application scope of electronic products, especially in fields such as magnetic drive robots, and nickel layer metal is easily affected by the environment due to its high surface energy. Causes electrochemical corrosion, lack of superhydrophobicity and weather resistance.
Laser-selective metallization and electroplating of nickel are used to form copper and nickel layers on the three-dimensional structure. Nickel is electroplating through specific current density and exposed to air, so that the nickel layer can obtain superhydrophobicity and ferromagneticity, and three-dimensionality is achieved by combining 3D printing technology. Preparation of patterned circuits.
It realizes the preparation of three-dimensional ferromagnetic superhydrophobic materials, with high conductivity, excellent weather resistance and patterning accuracy, and is suitable for communication antennas, electromagnetic shielding and magnetic drive robots, reducing production costs and polluting waste, suitable for large-scale production .
Smart Images

Figure BDA0005043909070000201 
Figure BDA0005043909070000211 
Figure BDA0005043909070000221
Abstract
Description
Technical Field
[0001] The invention relates to a three-dimensional ferromagnetic super-hydrophobic material and a preparation method and application thereof, belonging to the field of materials. Background Art
[0002] Nickel, as a ferromagnetic metal material, has good chemical stability and is widely used in electronic devices, corrosion-resistant coatings, magnetic actuators and other fields. Traditional manufacturing methods can produce patterned circuits on a two-dimensional plane through processes such as printed circuit boards, etching, and inkjet printing. However, two-dimensional manufacturing methods are not suitable for circuit conduction in three-dimensional structures, which severely limits the application scope of electronic products. The rise of 3D printing technology has made it possible to manufacture three-dimensional patterned circuits. People can directly manufacture wires and patterns with electrical functions on three-dimensional surfaces whose shapes can be freely customized, and directly install components on the three-dimensional surface to realize the manufacture of three-dimensional electronic products. Especially in communication antennas, electromagnetic shielding, flexible robots, etc., it is difficult to achieve them with traditional two-dimensional manufacturing methods.
[0003] In particular, for magnetically driven robots, there is a strong demand for three-dimensional customization of magnetic parts. Magnetic-driven robots are high-tech products that use magnetic fields to control the movement and deformation of robots. They have broad application prospects in the fields of medicine, bioengineering, micro-nano technology, etc. Magnetic-driven robots are usually composed of magnetic materials and soft materials, and can achieve movement and deformation through the control of external magnetic fields. For example, by locally heating the magnetic soft material to above the Curie temperature with a laser, the magnetic particles of the material are turned into paramagnets, and then a magnetic field is applied during the cooling process to redirect the magnetic domains of the magnetic particles, thereby realizing the programming and control of the soft robot.
[0004] At present, the nickel layer metal directly manufactured is still susceptible to environmental influences and electrochemical corrosion due to its high surface energy and certain hydrophilicity. The use of bionic structures to make the metal layer obtain super-hydrophobic properties can solve the electrochemical corrosion problem caused by the intrinsic hydrophilicity of the metal, thereby further improving the weather resistance of the metal layer.
[0005] Chinese patent application CN116277953A discloses a method for selective metallization of a nickel layer by hybrid additive manufacturing technology. However, the metal layer prepared by this method does not have super hydrophobicity, and the patent document does not mention whether the ferromagnetism of nickel can be guaranteed. In addition, this method uses a complex multi-material 3D printer, which not only increases the equipment cost, but also makes the type of 3D printing only applicable to the method provided in the article. Summary of the invention
[0006] The present invention provides a three-dimensional ferromagnetic super-hydrophobic material, which is suitable for communication antennas, electromagnetic shielding, and flexible robots, and is particularly suitable for the field of magnetically driven robots.
[0007] The present invention provides a three-dimensional ferromagnetic super-hydrophobic material, which is a three-dimensional structure material covered with a copper layer and a nickel layer in sequence;
[0008] The copper layer is prepared by brushing a mixture of a film-forming agent, a laser sensitizer and a solvent on the surface of a resin material, irradiating the surface with a laser after drying to form an activated pattern, and then selectively metalizing the activated area by chemical plating;
[0009] The nickel layer is obtained by electroplating nickel on a copper layer under a specific current density and then exposing the copper layer to air for more than 7 days to obtain a magnetic super-hydrophobic nickel layer.
[0010] Wherein, the usage percentage of the laser sensitizer and the film-forming agent is:
[0011] Laser sensitizer 5%-70%, film former 30%-95%; preferably, laser sensitizer 5%-20%, film former 80%-95%;
[0012] The film-forming agent is one or more of polyvinyl alcohol, polyvinyl pyrrolidone, acrylic acid copolymer, gelatin, agar, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, hydroxypropyl cellulose, hydroxypropyl methylcellulose, povidone, alcohol-soluble polyamide, acrylate homopolymer, acrylate copolymer, SEBS, SEPS, SBS, SIS, polyurethane, K resin, polycarbonate, styrene-maleic anhydride copolymer, and polystyrene; preferably, the film-forming agent is one of polyvinyl alcohol, hydroxypropyl cellulose, hydroxypropyl methylcellulose, alcohol-soluble polyamide, acrylate homopolymer, acrylate copolymer, SEBS, polycarbonate, and styrene-maleic anhydride copolymer;
[0013] The solvent is one or more of water, acetonitrile, methanol, ethanol, propanol, acetone, dioxane, tetrahydrofuran, methyl ethyl ketone, n-butanol, chloroform, ethyl bromide, benzene, chloropropane, toluene, carbon tetrachloride, carbon disulfide, cyclohexane, hexane, and heptane;
[0014] The laser sensitizer is one or more of a copper salt, a copper oxide, a copper hydroxide, an organic copper complex, a bismuth salt, a bismuth oxide, a bismuth hydroxide, an organic bismuth complex, a chromium salt, a chromium hydroxide, an organic chromium complex, a tin salt, a tin oxide, a tin hydroxide, an organic tin complex, a tin-doped oxide, an antimony salt, an antimony oxide, an antimony hydroxide, an organic antimony complex, a molybdenum salt, a molybdenum oxide, a molybdenum hydroxide, a molybdenum sulfide, a molybdenum hydroxide, an acid containing molybdenum, an indium salt, an indium oxide, an indium hydroxide, an organic indium complex, a zinc oxide, a zinc sulfide, a zinc hydroxide, a zinc salt, a tungsten oxide, a tungsten sulfide, an acid containing tungsten, a tungsten salt, a lanthanum oxide, a niobium oxide, a neodymium oxide, a nickel oxide, a nickel salt, a tellurium oxide, a zirconium oxide, a silver oxide, and a silver salt.
[0015] Among them, the material of the three-dimensional structure is prepared by a 3D printing method, and the 3D printing method includes any one of stereolithography (SLA), digital light processing (DLP), selective laser sintering (SLS), fused deposition modeling (FDM), multi-beam selective laser sintering (MJF), spraying powder molding (BJ), and direct energy deposition (DED).
[0016] Wherein, the wavelength of the laser is 300-1200nm, the laser power is 1-20W, the laser scanning speed is 1000-2000mm / s, and the laser frequency is 30-60kHz. Preferably, the wavelength is 1064nm, the laser power is 20W, and the laser frequency is 30kHz.
[0017] The electroplating solution used in the nickel plating is an aqueous solution containing 6.2g of boric acid, 23.8g of nickel chloride hexahydrate, and 26.3g of nickel sulfate per liter, with the plated piece as the cathode and the platinum sheet as the anode; the current density used in the electroplating is 100-500mA / cm 2 , the electroplating time is 5-20 minutes. Preferably, the nickel plating current density is: 100mA / cm 2 , electroplating time is 5-10 minutes.
[0018] Wherein, the placement time is 7-30 days.
[0019] Wherein, the water contact angle of the super hydrophobic nickel layer is greater than 150°, and the rolling angle is less than 5°.
[0020] The present invention provides a method for preparing the three-dimensional ferromagnetic super-hydrophobic material, which comprises the following steps:
[0021] Step S1: designing a three-dimensional structure of a three-dimensional electronic device according to requirements, and printing the designed three-dimensional structure using 3D printing technology;
[0022] Step S2: firstly mixing the film-forming agent with the solvent, then adding the laser sensitizer to obtain a laser sensitizer suspension or solution, then brushing the suspension or solution on the surface of the three-dimensional printed part, and then drying to remove the solvent;
[0023] Step S3: irradiating the surface of the three-dimensional component obtained in step S2 with a laser, forming an activation pattern in the irradiated area, and selectively metalizing the activated area by chemical plating to obtain a copper layer on the surface of the three-dimensional component;
[0024] Step S4: electroplating nickel on the copper layer obtained in step S3 for a certain period of time under a specific current density, and then exposing the nickel layer to air to obtain a three-dimensional ferromagnetic super-hydrophobic nickel layer.
[0025] The present invention provides use of the three-dimensional ferromagnetic super-hydrophobic material in preparing communication antennas, electromagnetic shielding, and flexible robots.
[0026] Wherein, the three-dimensional ferromagnetic super-hydrophobic material is used to prepare a magnetically driven robot.
[0027] When the inventors of the present invention used the nickel electroplating method to improve the weather resistance of the copper layer prepared by selective metallization, they unexpectedly discovered that after the copper layer was electroplated for a certain period of time using a specific current density, the obtained nickel layer could inherit the bionic microstructure on the surface of the copper layer, and by being exposed to the air for a period of time, it could spontaneously reach a super-hydrophobic state and have excellent ferromagnetism. This makes it possible to manufacture three-dimensional electronic products with excellent weather resistance. For example, for three-dimensional antennas or electromagnetic shielding structures exposed to the outside world, the method of the present invention can directly manufacture three-dimensional patterned circuits with super-hydrophobicity, while achieving functionality and also ensuring its corrosion resistance. Especially for magnetically driven robots, the present invention solves the problem of three-dimensional patterning of magnetic parts while ensuring its weather resistance.
[0028] Existing methods for selective metallization of nickel layers are all achieved by depositing the base part and the metallized part of the parts respectively by the method of multi-material three-dimensional printing, which makes the production of patterned metal layers must rely on a special three-dimensional printer and corresponding printing ink developed separately, greatly increasing manufacturing costs and production limitations. Compared with the existing methods, the present invention utilizes laser selective metallization and electroplating to directly prepare a ferromagnetic nickel layer with super-hydrophobicity, which has the advantages of good weather resistance, high production efficiency, convenient process, wide applicability, and high precision of the patterned metal layer obtained by laser selective metallization. In addition, there is also a method for obtaining super-hydrophobicity of the nickel layer by depositing low surface energy materials, but the nickel layer prepared by this method can directly obtain super-hydrophobicity by being exposed to air, which can significantly reduce the cost and polluting waste in the production process, and is suitable for large-scale production.
[0029] The three-dimensional ferromagnetic super-hydrophobic material of the present invention not only ensures the high conductivity and ferromagnetism of the nickel layer, but also enables the nickel layer to have excellent patterning accuracy and super-hydrophobicity. The above advantages make this nickel layer play an important role in the fields of high-precision electronic equipment, magnetic actuators, corrosion protection, self-cleaning, etc., and has broad application prospects in the direction of weather-resistant electronics.
[0030] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.
[0031] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. DETAILED DESCRIPTION
[0032] The raw materials and equipment used in the specific embodiments of the present invention are all known products and are obtained by purchasing commercially available products.
[0033] (1) The equipment information used in the present invention is as follows:
[0034] Stereolithography printer, model Form 3, manufactured by Formlabs Ltd.
[0035] Digital light processing printer, model DLP-D150, produced by Chuangxiang 3D Co., Ltd.;
[0036] Selective laser sintering printer, model Fuse 1, produced by Formlabs Ltd.
[0037] Fused deposition modeling printer, model F3300, produced by Stratasys Ltd.;
[0038] Laser marking machine, model MUV-ER, pulse laser marking machine, maximum laser power 5W, laser wavelength 355nm;
[0039] Laser marking machine, model DZ-Q, pulse laser marking machine, maximum laser power 8W, laser wavelength 395nm;
[0040] Laser marking machine, model MF-EA, fiber pulse laser marking machine, maximum laser power 20W, laser wavelength 1064nm;
[0041] Laser marking machine, model YK-F20G, semiconductor continuous laser marking machine, laser maximum power 10W, laser wavelength 533nm.
[0042] Laser marking machine, model BOT808-1000DT, fiber pulse laser marking machine, laser maximum power 7W, laser wavelength 808nm.
[0043] (2) The specific information of the resin used for three-dimensional printing of the present invention is as follows:
[0044] Stereolithography printing resins Somos GP and Somos Taurus were purchased from Stratasys Co., Ltd., Godart8001 was purchased from Zhongshan Dajian Technology Co., Ltd., and Elastic 50A Resin and White Resin V5 were purchased from Formlabs Co., Ltd. Digital light processing printing resins AmeraLabs AMD-3 and AmeraLabs TGM-7 were purchased from AmeraLabs Co., Ltd. Selective laser sintering printing resins Polypropylene Powder and TPU 90A Powder were purchased from Formlabs Co., Ltd. Fused deposition modeling printing resins ABS-M30 and ABS-ESD7 were purchased from Stratasys Co., Ltd.
[0045] (3) Coating fastness test:
[0046] According to ASTM D3359, use a grid cutter to draw a small square grid of 1mm×1mm on the coating area. Then, apply Scotch 3M 600-1PK test tape to the grid area and quickly tear off the tape. The grade of adhesion strength is determined based on the area where the metal layer falls off. In the ASTM D3359 grading standard, the higher the grade, the higher the adhesion between the polymer substrate and the coating. Among them:
[0047] The peeling area of 0B mesh is greater than 65%;
[0048] The peeling area of 1B grid is 35%-65%;
[0049] The peeling area of 2B mesh is 15%-35%;
[0050] The peeling area of 3B mesh is 5%-15%;
[0051] The spalling area of 4B mesh is 5%;
[0052] 5B has no mesh peeling.
[0053] (4) Water contact angle test:
[0054] The water contact angle on the surface of the nickel layer was measured using a contact angle meter. When the contact angle is greater than 150° and the rolling angle is less than 10°, the metal layer exhibits superhydrophobicity; when the contact angle is greater than 90° and less than 150° or the contact angle is greater than 150° and the rolling angle is greater than 10°, the metal layer exhibits hydrophobicity; when the contact angle is less than 90°, the metal layer exhibits hydrophilicity.
[0055] (5) Ferromagnetic test:
[0056] The ferromagnetism of the metal nickel layer is measured using a vibrating sample magnetometer. If the volume magnetic susceptibility χ of the nickel layer is greater than 10, the ferromagnetism is good.
[0057] Example 1
[0058] First, the designed three-dimensional structure is printed using a stereolithography printer Form 3, and the printing resin is Somos GP. The laser sensitizer copper hydroxide (10wt.%) is mixed with the film-forming agent water (42wt.%), polyvinyl alcohol (6wt.%), and ethanol (42wt.%) to obtain a laser sensitizer solution, and is brushed onto the surface of the printed three-dimensional component, and the solvent is dried to remove the solvent. The surface of the three-dimensional component brushed with the laser sensitizer is irradiated with a pulsed laser (1064nm) for laser activation, with a laser power of 20W, a scanning speed of 2000mm / s, and a laser frequency of 30kHz. Deionized water is used to wash away the excess laser sensitizer. According to the laser activation selective metallization chemical plating method and process known in the art, the three-dimensional component after laser activation is chemically copper plated. The chemical copper plating adopts a reduction system with formaldehyde as a reducing agent and copper sulfate as a metal copper salt. The resin composition is placed in a 45°C chemical copper plating solution for reaction for 40 minutes, and air is continuously introduced and stirred in the middle to ensure the uniformity of the copper layer. Finally, according to the nickel electroplating process known in the art, 100 mA / cm 2The conductive copper pattern was electroplated with nickel at a current density of 1.5047 W for 5 minutes to obtain a patterned ferromagnetic nickel layer. The plating solution used for nickel electroplating is an aqueous solution of boric acid (6.2 g / L), nickel chloride hexahydrate (23.8 g / L), and nickel sulfate (26.3 g / L), with the plated piece as the cathode and the platinum sheet as the anode. This electroplating solution is a phosphorus-free formula, and the nickel layer produced has good ferromagnetism. After the metal nickel layer was exposed to the air for 7 days, the water contact angle of the surface metal nickel layer was tested.
[0059] The test results are shown in Table 1.
[0060] Example 2
[0061] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (5wt.%), water (44wt.%), polyvinyl alcohol (7wt.%), ethanol (44wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0062] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0063] Example 3
[0064] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (15wt.%), water (40wt.%), polyvinyl alcohol (5wt.%), ethanol (40wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0065] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0066] Example 4
[0067] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (20wt.%), water (38wt.%), polyvinyl alcohol (4wt.%), ethanol (38wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0068] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0069] Example 5
[0070] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (25wt.%), water (35wt.%), polyvinyl alcohol (5wt.%), ethanol (35wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0071] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0072] Example 6
[0073] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (30wt.%), water (33wt.%), polyvinyl alcohol (4wt.%), ethanol (33wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0074] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0075] Example 7
[0076] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 14 days.
[0077] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0078] Example 8
[0079] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 21 days.
[0080] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0081] Example 9
[0082] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 15W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0083] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0084] Example 10
[0085] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 10W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0086] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0087] Embodiment 11
[0088] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 200mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0089] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0090] Example 12
[0091] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 300mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0092] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0093] Example 13
[0094] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 400mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0095] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0096] Embodiment 14
[0097] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 10 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0098] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0099] Embodiment 15
[0100] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 15 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0101] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0102] Example 16
[0103] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 20 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0104] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0105] Embodiment 17
[0106] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 40kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0107] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0108] Embodiment 18
[0109] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 50kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0110] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0111] Embodiment 19
[0112] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 60kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0113] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0114] Embodiment 20
[0115] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 355nm, the laser power was 5W, and the laser frequency was 30kHz. The current density of nickel electroplating was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0116] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0117] Embodiment 21
[0118] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 395nm, the laser power was 8W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0119] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0120] Embodiment 22
[0121] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 533nm, the laser power was 10W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0122] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0123] Embodiment 23
[0124] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 808nm, the laser power was 7W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0125] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0126] Embodiment 24
[0127] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was Somos Taurus, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0128] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0129] Embodiment 25
[0130] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was Godart 8001, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0131] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0132] Embodiment 26
[0133] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was Elastic 50AResin, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0134] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0135] Embodiment 27
[0136] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was White Resin V5, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0137] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0138] Embodiment 28
[0139] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a digital light processing printer DLP-D150, the resin used was AmeraLabs AMD-3, the laser sensitizer solution used was: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0140] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0141] Embodiment 29
[0142] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a digital light processing printer DLP-D150, the resin used was AmeraLabs TGM-7, the laser sensitizer solution used was: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0143] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0144] Embodiment 30
[0145] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used the selective laser sintering printer Fuse 1, the resin used Polypropylene Powder, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0146] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0147] Embodiment 31
[0148] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used the selective laser sintering printer Fuse 1, the resin used TPU 90A Powder, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0149] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0150] Embodiment 32
[0151] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a fused deposition modeling printer F3300, the resin used was ABS-M30, the laser sensitizer solution used was: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0152] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0153] Embodiment 33
[0154] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a fused deposition modeling printer F3300, the resin used was ABS-ESD7, the laser sensitizer solution used was: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0155] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0156] Embodiment 34
[0157] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used was: basic copper phosphate (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0158] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0159] Embodiment 35
[0160] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: zinc oxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0161] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0162] Embodiment 36
[0163] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: zinc hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0164] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0165] Embodiment 37
[0166] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper phosphate (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0167] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0168] Embodiment 38
[0169] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used was nickel acetate (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0170] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0171] Embodiment 39
[0172] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper oxalate (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0173] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0174] Embodiment 40
[0175] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), chloroform (84wt.%), polycarbonate (6wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0176] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0177] Embodiment 41
[0178] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used was: copper hydroxide (10wt.%), cyclohexane (84wt.%), SEBS (6wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0179] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0180] Embodiment 42
[0181] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), acetone (84wt.%), acrylate copolymer (6wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0182] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0183] Embodiment 43
[0184] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), acetone (84wt.%), acrylate homopolymer (6wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0185] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0186] Embodiment 44
[0187] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), ethanol (42wt.%), propanol (42wt.%), alcohol-soluble polyamide (6wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0188] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0189] Embodiment 45
[0190] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (84wt.%), styrene-maleic anhydride copolymer (6wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0191] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0192] Embodiment 46
[0193] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), hydroxypropyl cellulose (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0194] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0195] Embodiment 47
[0196] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), hydroxypropyl methylcellulose (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0197] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0198] Comparative Example 1
[0199] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: water (47wt.%), polyvinyl alcohol (6wt.%), ethanol (47wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0200] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0201] Comparative Example 2
[0202] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (2wt.%), water (46wt.%), polyvinyl alcohol (6wt.%), ethanol (46wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0203] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0204] Comparative Example 3
[0205] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 500mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0206] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0207] Comparative Example 4
[0208] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 700mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0209] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0210] Comparative Example 5
[0211] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 900mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0212] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0213] Comparative Example 6
[0214] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used was: basic copper phosphate (2wt.%), water (46wt.%), polyvinyl alcohol (6wt.%), ethanol (46wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0215] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0216] Comparative Example 7
[0217] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: zinc hydroxide (2wt.%), water (46wt.%), polyvinyl alcohol (6wt.%), ethanol (46wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0218] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0219] Comparative Example 8
[0220] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 10W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0221] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0222] Comparative Example 9
[0223] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 5W, and the laser frequency was 30kHz. The electroplating nickel current density was mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0224] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0225] Comparative Example 10
[0226] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 1 day.
[0227] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0228] Comparative Example 11
[0229] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 5 days.
[0230] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0231] Comparative Example 12
[0232] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 355nm, the laser power was 1W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0233] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0234] Comparative Example 13
[0235] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 395nm, the laser power was 1W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0236] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0237] Comparative Example 14
[0238] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 30 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0239] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0240] Comparative Example 15
[0241] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 40 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0242] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0243] Comparative Example 16
[0244] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 90kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0245] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0246] Comparative Example 17
[0247] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl alcohol (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 100kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0248] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0249] Comparative Example 18
[0250] Nickel is electroplated directly on the surface of commercial conductive copper foil. The electroplating current density is 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0251] Other test methods are the same as those in Example 1. The test results are shown in Table 1.
[0252] Comparative Example 19
[0253] Nickel is electroplated directly on the surface of commercial conductive copper foil. The electroplating current density is 300mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0254] Other test methods are the same as those in Example 1. The test results are shown in Table 1.
[0255] Comparative Example 20
[0256] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), polyvinyl pyrrolidone (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0257] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0258] Comparative Example 21
[0259] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (42wt.%), gelatin (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0260] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0261] Comparative Example 22
[0262] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used was: copper hydroxide (10wt.%), water (42wt.%), agar (6wt.%), ethanol (42wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0263] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0264] Comparative Example 23
[0265] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the three-dimensional printing method used a stereolithography printer Form 3, the resin used was SomosGP, the laser sensitizer solution used: copper hydroxide (10wt.%), water (45wt.%), ethanol (45wt.%), the laser wavelength was 1064nm, the laser power was 20W, and the laser frequency was 30kHz. The electroplating nickel current density was 100mA / cm 2 , the electroplating time is 5 minutes. After nickel electroplating, the nickel layer is exposed to air for 7 days.
[0266] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0267] Comparative Example 24
[0268] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the nickel plating method was chemical plating, the plating solution was an aqueous solution of NiSO4·6H2O (25 g / L), Na3C6H5O7·2H2O (30 g / L), CH3COONa (20 g / L), and Na2H2PO2·H2O (30 g / L), and the chemical plating time was 40 minutes. After nickel plating, the nickel layer was exposed to air for 7 days.
[0269] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0270] Comparative Example 25
[0271] The three-dimensional component, laser sensitizer solution and activated component were prepared by referring to the method of Example 1, except that the nickel plating method was chemical plating, the plating solution was an aqueous solution of NiSO4·6H2O (25 g / L), Na3C6H5O7·2H2O (30 g / L), CH3COONa (20 g / L), and Na2H2PO2·H2O (30 g / L), and the chemical plating time was 70 minutes. After nickel plating, the nickel layer was exposed to air for 7 days.
[0272] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0273] Comparative Example 26
[0274] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the nickel plating method was chemical plating, the plating solution was an aqueous solution of NiSO4·6H2O (25 g / L), Na3C6H5O7·2H2O (30 g / L), CH3COONa (20 g / L), and Na2H2PO2·H2O (30 g / L), and the chemical plating time was 40 minutes. After nickel plating, the nickel layer was exposed to air for 14 days.
[0275] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0276] Comparative Example 27
[0277] The three-dimensional component, laser sensitizer solution and activated component were prepared by referring to the method of Example 1, except that the nickel plating method was chemical plating, and the plating solution composition was NiSO4 (30 g / L), NaH2PO2 (20 g / L), C6H 17 The electroless plating time is 40 minutes with an aqueous solution of N3O7 (50 g / L). After nickel plating, the nickel layer is exposed to air for 7 days.
[0278] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0279] Comparative Example 28
[0280] The three-dimensional component, laser sensitizer solution and activated component were prepared according to the method of Example 1, except that the nickel plating method was chemical plating, the plating solution was an aqueous solution of NiCl2 (30 g / L), NaH2PO2 (10 g / L), and NH4Cl (50 g / L), and the chemical plating time was 40 minutes. After nickel plating, the nickel layer was exposed to air for 7 days.
[0281] The test method is the same as that in Example 1. The test results are shown in Table 1.
[0282] When the polymer surface cannot be laser activated for selective metallization or has no testing value, the performance test cannot be performed and is therefore indicated as “no performance”.
[0283] Table 1 Summary of raw material parameters “None” means that the corresponding substance or method was not used.
[0284] Table 1 Performance test results of Examples 1 to 38 and Comparative Examples 1 to 13
[0285]
[0286]
[0287]
[0288]
[0289]
[0290]
[0291]
[0292]
[0293]
[0294]
[0295]
[0296] It can be seen from the test results in Table 1 that Examples 1 to 47 utilize laser selective metallization combined with nickel electroplating, and successfully achieve the preparation of a patterned superhydrophobic nickel layer on the three-dimensional resin surface by using different three-dimensional printing methods, different three-dimensional resins, different laser sensitizers and contents, different film-forming agents, different laser wavelengths, different laser powers, different laser frequencies, different electroplating current densities, different electroplating times, and different placement times in the air.
[0297] From the test results in Table 1, it can be seen that comparative example 1 does not add laser sensitizer and cannot be plated; comparative examples 2 and comparative examples 6-7 have a laser sensitizer content of less than 4wt.%, and cannot be plated or the coating bonding strength after partial plating is low and has no practical value; comparative examples 3-5 nickel plating current is greater than 500mA / cm 2 , although it can be plated normally, it cannot achieve super-hydrophobicity, and the bonding fastness of the coating decreases; Comparative Examples 8-9, Comparative Examples 12-13 The laser power is less than 50% of the maximum power of the laser, and the nickel layer cannot be plated normally; Comparative Examples 10 and Comparative Examples 11 are exposed to the air for less than 6 days, and the nickel layer cannot achieve super-hydrophobicity; Comparative Examples 14-15 The nickel plating time is greater than 20 minutes, although it can be plated normally, the nickel layer cannot achieve super-hydrophobicity; Comparative Examples 16-17 The laser frequency is greater than 60kHz and cannot be plated; Comparative Examples 18-19 directly electroplated nickel on the surface of commercial conductive copper foil, and the nickel layer cannot obtain super-hydrophobicity; Comparative Examples 20-23 did not use polyvinyl alcohol, ethylene-vinyl acetate copolymer, hydroxypropyl cellulose, hydroxypropyl methylcellulose as a film-forming agent or did not use a film-forming agent, and could not be plated. Comparative Examples 24-28 The nickel plating method uses chemical plating, and the nickel layer cannot obtain super-hydrophobicity, and because the plating solution contains phosphorus, the coating is non-magnetic.
[0298] Combining the experimental results of the embodiments and comparative examples, it can be seen that when the amount of laser sensitizer added is 5-20wt.%, the metal layer can be plated normally and the amount of sensitizer used can be most balanced. When the film-forming agent component is selected from polyvinyl alcohol, hydroxypropyl cellulose, hydroxypropyl methylcellulose, alcohol-soluble polyamide, acrylate homopolymer, acrylate copolymer, SEBS, polycarbonate, styrene-maleic anhydride copolymer, it can be successfully plated. When the laser power is 100% of the maximum power of the laser and the laser frequency is 30kHz, the effect of laser activation is best. The nickel plating current density adopts 100mA / cm 2 When the electroplating time is controlled within 5-10 minutes, the super hydrophobic effect of the nickel layer is the best. After the coating is exposed to the air for seven days, it can obtain excellent super hydrophobic properties.
[0299] In summary, the three-dimensional ferromagnetic super-hydrophobic material provided by the present invention has no special requirements for the three-dimensional printing method, can spontaneously obtain super-hydrophobicity without artificial modification, the pattern can be freely customized, and the ferromagnetism of the nickel layer is guaranteed, which is of great significance in the anti-corrosion, self-cleaning, anti-scaling, anti-icing and other weather resistance of the conductive metal layer. The method uses laser for selective metallization and does not rely on artificial low surface energy material deposition. It has the advantages of high precision, low cost and high universality, and has broad application prospects in the three-dimensional electronic technology industry.
Claims
1. A three-dimensional ferromagnetic super-hydrophobic material, characterized in that: It is a three-dimensional structure material covered with copper layer and nickel layer in sequence; The copper layer is prepared by brushing a mixture of a film-forming agent, a laser sensitizer and a solvent on the surface of a resin material, irradiating the surface with a laser after drying to form an activated pattern, and then selectively metalizing the activated area by chemical plating; The nickel layer is obtained by electroplating nickel on a copper layer under a specific current density and then exposing the copper layer to air for more than 7 days to obtain a magnetic super-hydrophobic nickel layer.
2. The three-dimensional ferromagnetic super-hydrophobic material according to claim 1, characterized in that: The percentage of the laser sensitizer and the film-forming agent is: Laser sensitizer 5%-70%, film former 30%-95%; preferably, laser sensitizer 5%-20%, film former 80%-95%; The film-forming agent is one or more of polyvinyl alcohol, polyvinyl pyrrolidone, acrylic acid copolymer, gelatin, agar, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, hydroxypropyl cellulose, hydroxypropyl methylcellulose, povidone, alcohol-soluble polyamide, acrylate homopolymer, acrylate copolymer, SEBS, SEPS, SBS, SIS, polyurethane, K resin, polycarbonate, styrene-maleic anhydride copolymer, and polystyrene; preferably, the film-forming agent is one of polyvinyl alcohol, hydroxypropyl cellulose, hydroxypropyl methylcellulose, alcohol-soluble polyamide, acrylate homopolymer, acrylate copolymer, SEBS, polycarbonate, and styrene-maleic anhydride copolymer; The solvent is one or more of water, acetonitrile, methanol, ethanol, propanol, acetone, dioxane, tetrahydrofuran, methyl ethyl ketone, n-butanol, chloroform, ethyl bromide, benzene, chloropropane, toluene, carbon tetrachloride, carbon disulfide, cyclohexane, hexane, and heptane; The laser sensitizer is one or more of a copper salt, a copper oxide, a copper hydroxide, an organic copper complex, a bismuth salt, a bismuth oxide, a bismuth hydroxide, an organic bismuth complex, a chromium salt, a chromium hydroxide, an organic chromium complex, a tin salt, a tin oxide, a tin hydroxide, an organic tin complex, a tin-doped oxide, an antimony salt, an antimony oxide, an antimony hydroxide, an organic antimony complex, a molybdenum salt, a molybdenum oxide, a molybdenum hydroxide, a molybdenum sulfide, a molybdenum hydroxide, an acid containing molybdenum, an indium salt, an indium oxide, an indium hydroxide, an organic indium complex, a zinc oxide, a zinc sulfide, a zinc hydroxide, a zinc salt, a tungsten oxide, a tungsten sulfide, an acid containing tungsten, a tungsten salt, a lanthanum oxide, a niobium oxide, a neodymium oxide, a nickel oxide, a nickel salt, a tellurium oxide, a zirconium oxide, a silver oxide, and a silver salt.
3. The three-dimensional ferromagnetic super-hydrophobic material according to claim 1, characterized in that: The material of the three-dimensional structure is prepared by a 3D printing method, and the 3D printing method includes any one of stereolithography (SLA), digital light processing (DLP), selective laser sintering (SLS), fused deposition modeling (FDM), multi-beam selective laser sintering (MJF), spraying powder molding (BJ), and direct energy deposition (DED).
4. The three-dimensional ferromagnetic super-hydrophobic material according to claim 1, characterized in that: The wavelength of the laser is 300-1200nm, the laser power is 1-20W, the laser scanning speed is 1000-2000mm / s, and the laser frequency is 30-60kHz; preferably, the wavelength is 1064nm, the laser power is 20W, and the laser frequency is 30kHz.
5. The three-dimensional ferromagnetic super-hydrophobic material according to claim 1, characterized in that: The electroplating solution used in the nickel plating is an aqueous solution containing 6.2g of boric acid, 23.8g of nickel chloride hexahydrate, and 26.3g of nickel sulfate per liter, with the plated piece as the cathode and the platinum sheet as the anode; the current density used in the electroplating is 100-500mA / cm 2 , the electroplating time is 5-20 minutes; preferably, the nickel plating current density is: 100mA / cm 2 , electroplating time is 5-10 minutes.
6. The three-dimensional ferromagnetic super-hydrophobic material according to claim 1, characterized in that: The placement time is 7-30 days.
7. The three-dimensional ferromagnetic super-hydrophobic material according to any one of claims 1 to 6, characterized in that: The water contact angle of the super hydrophobic nickel layer is greater than 150°, and the rolling angle is less than 5°.
8. A method for preparing the three-dimensional ferromagnetic super-hydrophobic material according to any one of claims 1 to 6, characterized in that: It includes the following steps: Step S1: designing a three-dimensional structure of a three-dimensional electronic device according to requirements, and printing the designed three-dimensional structure using 3D printing technology; Step S2: firstly mixing the film-forming agent with the solvent, then adding the laser sensitizer to obtain a laser sensitizer suspension or solution, then brushing the suspension or solution on the surface of the three-dimensional printed part, and then drying to remove the solvent; Step S3: irradiating the surface of the three-dimensional component obtained in step S2 with a laser, forming an activation pattern in the irradiated area, and selectively metallizing the activated area by chemical plating to obtain a copper layer on the surface of the three-dimensional component; Step S4: electroplating nickel on the copper layer obtained in step S3 for a certain period of time under a specific current density, and then exposing the nickel layer to air to obtain a three-dimensional ferromagnetic super-hydrophobic nickel layer.
9. Use of the three-dimensional ferromagnetic super-hydrophobic material according to any one of claims 1 to 7 in the preparation of communication antennas, electromagnetic shielding, and flexible robots.
10. The use according to claim 9, characterized in that: The three-dimensional ferromagnetic super-hydrophobic material is used to prepare a magnetically driven robot.
Citation Information
Patent Citations
Super-hydrophobic cobalt plating of metal surface and preparation method for super-hydrophobic cobalt plating
CN103382564A
Method for preparing nickel-cobalt plating by brush plating on copper alloy surface
CN108193242A
Air electrode of super-hydrophobic metal-air battery as well as preparation method and application
CN112736255A
Method for directly preparing super-hydrophobic copper layer through laser activation selective metallization
CN117604509A
Electroless plating method using laser penetration method
KR102218792B1
